Impact of changing the surgical team for wound closure on surgical site infection: A matched case-control study. - Lilian Salm; Dimitri Chapalley; Stéphanie Fabienne Perrodin; Franziska Tschan; Daniel Candinas; Guido Beldi (PLoS ONE, 2020)
Background Wound closure is performed at the end of the procedure, when the attention of the surgical team may decrease due to tiredness. The aim of this study was to assess the influence of changing the surgical team for wound closure on the rate of surgical site infection (SSI). Methods A two-armed observational monocentric matched case-control study was performed in a time series design. During the baseline period, closure of the abdominal wall was performed by the main surgical team. The intervention consisted of closure of the abdominal wall and skin by an independent surgical team. Matching was based on gender, BMI, length of surgery, type of surgery, elective versus emergency surgery and ASA score. The primary outcome was SSI rate 30 days after surgery. Results A total of 72 patients in the intervention group were matched with 72 patients in the baseline group. The SSI rate after 30 days in the intervention group was 10% (n = 7) and in the baseline group 21% (n = 15) (p = 0.064). Redo-Surgery as result of infection (e.g. opening the wound, drainage or reoperation) was significantly higher in the baseline group (19.4% vs 2.7%; p = 0.014). Mortality, length of stay, rehospitalisation and complication rates 30 days after surgery did not differ significantly. Conclusion Changing the surgical team for wound closure did not reduce the overall rate of SSI, but the rate of redo-surgery as a result of SSI. Despite being potentially beneficial, organizational factors are a main limiting factor of changing the surgical team for the wound closure. Trial registration Clinicaltrial.gov NCT04503642.